Lir´ot im ani mechajechet . To See if I'm Smiling - Yarom, Tamar (Yarom, Tamar, 2007)
Verzio FF Israel is the only country in the world where 18-year-old girls are drafted for compulsory military service. To See If I’m Smiling takes a look at the actions and behavior of women soldiers in the Israeli army stationed in the Gaza Strip and the West Bank. The women who have tried to bury the past for years, finally speak openly about their experiences. Deeply personal interviews are dramatically interwoven with both archival footage and details of the women’s daily lives. One woman recounts how she posed for a photo with a Palestinian corpse. She searches for that picture, saying, “I wanted to see if I’m smiling.” At a time when women in the military are increasingly on the frontlines, this powerful film explores the ways that gender, ethics, and moral responsibility intersect during war.